Dorsal Colour Patterns of Asian Water Monitor, Varanus salvator Collected for Trade in Cirebon, Indonesia - Elika Boscha; Evy Arida; Donan Satria Yudha (Journal of Tropical Ethnobiology, 2020)
The Asian water monitor, Varanus salvator, has been exploited for its skin and meat in Indonesia. We found evidence of trade on this species in the greater Cirebon area in the province of Jawa Barat and linked the trade to raw skin supplies for local craft markets. Skins of water monitor distributed on Java were unique in their pattern, where a series of yellowish and dark grey scales that form a round shape called ocelli are arranged into two compact transverse bands on the back near the front limbs. This unique pattern found in our sample may be useful to identify the origin of skins collected for trade and the subsequent craft products. However, this pattern was absent in the craft products available for display in one of the warehouses visited for this study. On the other hand, we observed stockpiles of water monitor raw skins at the warehouses and found a slight difference in the dorsal color pattern. These raw skins in stock were lacking in “double banded” pattern on the dorsal side and were likely to be originated from other areas in Indonesia, possibly Sumatra or Kalimantan. Live animals for sale at the warehouses maybe used for other purposes than to supply materials for local craft industry, for example meat consumption or feed for catfish.